Intellectual Situations In (Elia Abu Madhi) poetry - Al-Janabi, Hassan Ghanem Fadala; Al- Husainy, Faris Azeez Muslim (International Journal of Psychosocial Rehabilitation, 2020)
This study deals with the most important intellectual situations (positions) of a poet from the NorthDiaspora, that he is the most prominent poet of (the pen association) who is the famous poet (Elia Abu Madhi)